we know that cos^2(x) = 1/2(1+cos(2x)) could I say that cos^2(3x)=1/2(1+cos(6x)) ?
doomgaze Apr 2009 37 2 May 10, 2010 #1 we know that \(\displaystyle cos^2(x) = 1/2(1+cos(2x))\) could I say that \(\displaystyle cos^2(3x)=1/2(1+cos(6x)) \) ?
we know that \(\displaystyle cos^2(x) = 1/2(1+cos(2x))\) could I say that \(\displaystyle cos^2(3x)=1/2(1+cos(6x)) \) ?
S sa-ri-ga-ma Jun 2009 806 275 May 10, 2010 #2 doomgaze said: we know that \(\displaystyle cos^2(x) = 1/2(1+cos(2x))\) could I say that \(\displaystyle cos^2(3x)=1/2(1+cos(6x)) \) ? Click to expand... Difinetly you can say so.
doomgaze said: we know that \(\displaystyle cos^2(x) = 1/2(1+cos(2x))\) could I say that \(\displaystyle cos^2(3x)=1/2(1+cos(6x)) \) ? Click to expand... Difinetly you can say so.
doomgaze Apr 2009 37 2 May 10, 2010 #3 sa-ri-ga-ma said: Difinetly you can say so. Click to expand... I guess more importantly is it correct?
sa-ri-ga-ma said: Difinetly you can say so. Click to expand... I guess more importantly is it correct?
S sa-ri-ga-ma Jun 2009 806 275 May 10, 2010 #5 doomgaze said: I guess more importantly is it correct? Click to expand... If 3x= t 6x= 2t. cos(2t) = 2cos^2(t) - 1 so 2cos^2(t) = 1+cos(2t) cos^2(t) = 1/2(1+cos(2t)) replace t by 3x and find the result.
doomgaze said: I guess more importantly is it correct? Click to expand... If 3x= t 6x= 2t. cos(2t) = 2cos^2(t) - 1 so 2cos^2(t) = 1+cos(2t) cos^2(t) = 1/2(1+cos(2t)) replace t by 3x and find the result.